Taking OAB seriously: A qualitative evaluation of primary care education on overactive bladder syndrome management - Turell, Wendy (Int J Clin Pract, 2020)
BACKGROUND: Overactive bladder (OAB) syndrome has a diverse etiology that disrupts quality of life domains in affected patients. OAB is significantly under‐recognised and undertreated, especially in the primary care setting. In order to educate primary care providers about OAB recognition, evaluation and management, we created a virtual live‐streamed and enduring education program. METHODS: We evaluated the impact of education on provider knowledge and self‐efficacy via qualitative interviews with a sample of education participants. We analysed participant responses via constant comparative method, an iterative approach that allows for exploration of a priori issues and identification of emergent themes. RESULTS: We identified four key themes: (a) taking OAB seriously; (b) variations in therapy; (c) patient motivation; and (d) education value. Participants were proactive about screening for and managing OAB and recognised urgency as a key symptom; some participants used diagnostic tests that are not are not considered necessary in the workup of uncomplicated OAB patients. Participants varied in their descriptions of initial approaches to treatment and most participants described a longer‐than‐recommended follow‐up window to monitor patients. Some participants characterised patients as looking for a “quick fix” in ways that could lead to provider inaction in relation to behavioural/lifestyle interventions. Overall, participants felt that the education validated their current practice and provided new knowledge about evaluation, initiating behavioural treatment, and combination therapy. CONCLUSIONS: Participant responses were congruent with education messages, which likely reflect their “readiness to learn”. The rationale for diagnostic tests and evidence on the effectiveness of behavioural regimens represent ongoing areas of unmet educational need.